Simulation Model of Infinite Perishable Queueing Inventory System with Feedback - Shahmaliyev, Mammad (Управляющие системы и машины, 2018)
Perishable Queuing Inventory system with positive service time and customer feedback is considered. The system applies Variable Size Order policy for the inventory replenishment. Stochastic simulation method is used to calculate the system performance measures and find its stationary distribution. The dependence of performance measures on the reorder level is illustrated and analyzed using the numerical experiments.